Research on the core competitiveness of smart phone human-computer interaction. (July 2021) - Kou, Yuanyuan; Chen, Huiying; Zhou, Yanping
Abstract: Identifying the core technique in the field of human-computer interaction is beneficial to improve international technical competitiveness of enterprise. By means of patent data of domestic and foreign smart phone, with the adoption of patent portfolio analysis model, it has exploration and research on the core competitiveness of human-computer interaction of smart phone from four aspects: enterprise, technology, inventor, and patent-market integration. The results show that human-computer interaction is the core field of smartphones; Although the overall technical level of Chinese enterprises in the field of human-computer interaction is lower than that of foreign enterprises, China has an advantage in the wireless communication network (H04W), which is the core and cutting-edge technology in the field of human-computer interaction; Enterprises in the world have similar proportions of high-level research and development talents, without absolute industry benchmark in which both technology and market dominate.